"As We Talk About This More, a Box Opens Up": Family Literacy Programs for Fathers in Treatment for Substance Use Disorder. Issue 4 (19th December 2020) - Wiseman, Angela M.; Atkinson, Ashley A.; Cryer‐Coupet, Qiana R.
Abstract: Parenting while transitioning out of incarceration, homelessness, or drug addiction has received inadequate attention despite the fact that these factors affect more and more of the U.S. population each day. This article is about a family literacy program implemented in a residential treatment facility where the fathers, most of whom were previously incarcerated and now receiving treatment for substance use disorder, have been parenting from afar with limited access to their children. Fathers participated in a family literacy program where they respond to children's literature with the intention of eventually reading with their children. Our research was guided by the following question: How do fathers who are separated from their children while in a residential treatment program, read and respond to children's literature in a small‐group setting? Findings reflect how fathers wanted to share their feelings about parenting and also consider their identities as fathers who were also addicts.